2004
DOI: 10.2166/wst.2004.0463
|View full text |Cite
|
Sign up to set email alerts
|

North American performance experience with anoxic and anaerobic selectors for activated sludge bulking control

Abstract: Obtaining reliably high compaction characteristics and low SVI values has enormous economic consequences on activated sludge plant design and operation. Now that use of selectors has become more common for achieving low SVI values, the assessment of the full-scale performance characteristics of activated sludge plants incorporating selectors has high value for the design and operation of future plants. Treatment plant effluent quality is seldom analyzed solely on an average basis and the impact peak events hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 0 publications
0
12
0
2
Order By: Relevance
“…The superior effluent quality of EF-PDMLE without a final aerobic stage is notable, since the final aerobic stage has been commonly applied to prevent deterioration in solids/liquid separation efficiency [7]. Several studies have reported that the flotation efficiency decreased as the SVI 30 of the sludge increased [10,16,17].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The superior effluent quality of EF-PDMLE without a final aerobic stage is notable, since the final aerobic stage has been commonly applied to prevent deterioration in solids/liquid separation efficiency [7]. Several studies have reported that the flotation efficiency decreased as the SVI 30 of the sludge increased [10,16,17].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, how to increase the biomass in the bioreactor is a big challenge for the success of the post-denitrification application. In addition, the post-denitrification has difficulty of application to the final stage of process without an aerobic stage due to deterioration of the activated sludge settleability and solids/ liquid separation efficiency by denitrification [7].…”
Section: Introductionmentioning
confidence: 99%
“…There have also been reports showing that anoxic selectors were also able to improve the settleability of sludges in full-scale activated sludge systems (Marten and Daigger, 1997). The performance of several activated sludge plants incorporating anoxic and anaerobic selectors has recently been evaluated in the USA (Parker et al, 2003). The results show that the settleability of the sludge was significantly improved after the installation of the selectors.…”
Section: Introductionmentioning
confidence: 98%
“… El protocolo STOWA  El protocolo BIOMATH (Vanrolleghem et al, 2003)  El protocolo WERF para calibración del modelado (Melcer et al, 2003)  Las guías Hochschulgruppe (HSG) (Langergraber et al, 2004).…”
Section: Protocolos De Caracterizaciónunclassified
“…El beneficio de los selectores en la reducción de organismos filamentosos (Harper y Jenkins, 2003) mejora el índice volumétrico de lodos y reduce la probabilidad de que se genere un lodo voluminoso de baja sedimentabilidad y disminuye la posible expansión de los mantos de lodo en los calificadores secundarios (Jang y Schuler, 2007). Parker et al (2003) estudió 21 plantas de tratamiento que contaban con selectores anóxicos y anaerobios, y reportó que todas las plantas mostraron una mejoría después de la instalación de los selectores. 70% de las plantas que contaban con selectores anóxicos alcanzaron índices volumétricos de lodo (IVL) inferiores a los 200 ml/g, mientras que 90% de las plantas con selectores anaerobios mostraron IVL menores de 150 ml/g.…”
Section: El Rol De Los Selectoresunclassified